PENERAPAN PROBLEM BASED LEARNING (PBL) MENGGUNAKAN BAHAN PANGAN UNTUK MENINGKATKAN BERPIKIR KRITIS ANAK: APPLICATION OF PROBLEM BASED LEARNING (PBL) USING FOOD TO IMPROVE CHILDREN'S CRITICAL THINKING - Sriyanto, Agus; Farihah, Elyaum (JOURNAL FASCHO : JURNAL PENELITIAN DAN PENDIDIKAN ANAK USIA DINI, 2023)
The purpose of this study was to improve the critical thinking ability of AUD in group A of TK Tunas Rimba Ngawi Kab. Ngawi. The research that the researchers took was action research, carried out as many as fourteen meetings. Group A of Tunas Rimba Ngawi Kindergarten totaling 12 children was the subject of the study. The research steps that researchers take include: (1) planning, (2) implementation / action, (3) observation / observation, and (4) reflection. The instruments that researchers use are observation sheets, interview transcripts, and documentation. Based on the results of the analysis, the average class in the pre-cycle was 66.56%, cycle one increased by 69.56%, and in cycle two increased to 78.01%.